Genome sequencing and phylogenetic analysis of allotetraploid Salix matsudana Koidz. (1st December 2020) - Zhang, Jian; Yuan, Huwei; Li, Yujuan; Chen, Yanhong; Liu, Guoyuan; Ye, Meixia; Yu, Chunmei; Lian, Bolin; Zhong, Fei; Jiang, Yuna; Xu, Jichen
Abstract: Polyploidy is a common phenomenon among willow species. In this study, genome sequencing was conducted for Salix matsudana Koidz (also named Chinese willow), an important greening and arbor tree species, and the genome of this species was compared with those of four other tree species in Salicaceae. The total genome sequence of S. matsudana was 655.72 Mb in size, with repeated sequences accounting for 45.97% of the total length. In total, 531.43 Mb of the genome sequence could be mapped onto 38 chromosomes using the published genetic map as a reference. The genome of S. matsudana could be divided into two groups, the A and B genomes, through homology analysis with the genome of Populus trichocarpa, and the A and B genomes contained 23, 985 and 25, 107 genes, respectively. 4DTv combined transposon analysis predicted that allotetraploidy in S. matsudana appeared ~4 million years ago. The results from this study will help reveal the evolutionary history of S. matsudana and lay a genetic basis for its breeding.